IDEAL (Identify, Define, Explore, Act, Look Back) Metacognitive-STAD Cooperative Learning to Improve Students’ Self-Efficacy and Problem-Solving Ability - Ardianty, Annida Elfiana Citra; Parlan, Parlan; Yahmin, Yahmin (J-PEK (Jurnal Pembelajaran Kimia), 2023)
This study aims to determine the effectiveness of IDEAL-type metacognitive combined with STAD cooperative learning to improve students' self-efficacy and problem-solving abilities in thermochemistry. The research design used was a Quasi-Experimental Pretest-Postest Control Group Design and a 2 x 2 factorial design. The experimental class was taught with the IDEAL type metacognitive learning strategy combined with STAD cooperative learning, while the control class was taught with the STAD cooperative learning model. The data analysis technique used is descriptive analysis and different tests. The results showed that the IDEAL type metacognitive learning strategy combined with STAD cooperative learning was more effective in improving students' problem-solving abilities than the STAD cooperative learning model. However, it is not effective in increasing students' self-efficacy. Suppose students are taught with the IDEAL type metacognitive learning strategy combined with STAD cooperative learning and accompanied by high learning motivation. In that case, the students' self-efficacy and problem-solving abilities also increase even though the interaction between the two is weak. REFERENCESAriff, S.S., Kumar, S.V., Azizi, M.N., & Hilmi, F. 2022. Relationship between Self-Efficacy and Academic Motivation among University and College Students Enrolled in Kuala Lumpur during Movement Control Period (MCO). Journal of Positive School Psychology. 6(3)3362-3374.Aswita, Rusman, & Rahmayani, R.F.I. (2017). Identification of Students' Difficulties in Understanding Thermochemistry Materials by Using a Three-Tier Multiple Choice Diagnostic Instrument in Class XI MIA 5 MAN MODEL Banda Aceh. Jurnal Pendidikan Ilmiah Mahasiswa Pendidikan Kimia. 2(1)35-44.Ayunia, R., & Marlena, N. (2022). The Effect of Learning Motivation and Self Efficacy on Problem Solving Ability on Students Faculty of Economics and Business Unesa. Jurnal Mantik. 6(1)599-608.Bandura. (1977). Self-Efficacy: Toward a Unifying Theory of Behavioral Change. Psychol Rev.Bardach, E., & Patashnik, E.M. (2019). A Practical Guide for Policy Analysis: The Eightfold Path to More Effective Problem-Solving. CQ Press.Bransford , J., &B.S. Stein. (1993). The IDEAL Problem Solver: A Guide for Improving Thinking, Learning, and Creativity (2nd ed). New York: W.H. Freeman.Demirdogen, B. (2017). Examination of Chemical Representation on Turkish High School Chemistry Textbook. Journal of Baltic Science Education. 16(4): 472 – 499.Erna, M. R., Rery, U., & Astuti, W. (2018). Improving Students' Critical Thinking Skills on Thermochemistry Materials at Pekanbaru High School through the Application of Process Oriented Guided Inquiry Learning (POGIL) Learning Strategies. Jurnal Roset Pendidikan Kimia. 8(1)17-27.Fatimah, Nurhidayah, Ahmad, H., Febryanti, & Ali, M.P. (2018). Motivation to Learn is a Factor Supporting The Achievement of Students' Problem Solving Abilities. Advances in Social Science, Education and Humanities Research (ASSEHR). 227.101-104.Griffin, P., & Care, E. (2015). Assessment and teaching of 21st century skills: method and approach . New York:Springer.Güss, C.D., Burger, M.L., & Dörner, D. (2017). The Role of Motivation in Complex Problem Solving. Frontiers in Psychology. 8(851)1-5.Harahap, I.H. (2021). Correlation Between Learning Motivation and Problem-Solving Ability Based on Gender. Al-Ishlah: Jurnal Pendidikan. 13(3) 2811-2816.Hasbullah, & Wibawa, B. 2017. Upaya Analysis of Mathematics Students Ability in Learning Metacognitive Strategy Type Ideal (Identify, Define, Explore, Act, Look). International Electronic Journal of Mathematics Education. 12(3)859-872.Husna, I.A., & Kurniasih, A.W. (2019). Student's Creative Thinking Ability in Problem-Posing Activities Viewed from Self-Efficacy. UNNES Journal of Mathematics Education. 8(3)202-208.Hutajulu, M., Wijaya, T.T., & Hidayat, W. (2019). The Effect Of Mathematical Disposition And Learning Motivation On Problem Solving: An Analysis. Journal of Mathematics Education. 8(2)229-238.Indriyani, R.W. (2016). Application of the IDEAL Problem Solving Learning Model in Solving Mathematical Problems on Perimeter and Area of Rectangle and Square Materials for Grade VII Students of Middle School. MATHEdunesa: Jurnal Ilmiah Pendidikan Matematika. 5(2)100-108.Ishtiaq, M., Ali, Z., & Salem, M. (2017). An Experimental Study of the Effect of Student Teams Achievement Divisions (STAD) on Vocabulary Learning of EFL Adult Learners. Arab World English Journal (AWEJ). 8(3)356-375.Kumar, A. & Singh, A.P. (2016). Effect of Student Teams Achievement Divisions (STAD) Method on Problem Solving Ability in Relation to Critical Thinking. International Journal of Advanced Research and Development. 1(7)26-30.Kurnia, L.D., Haryati, S., & Linda, R. (2022). Development of a Higher Order Thinking Skills Evaluation Instrument Using Quizizz on Thermochemistry Materials to Improve Students' Higher Order Thinking Ability. Jurnal Pendidikan Sains Indonesia. 10(1)176-190.Kurniawan, E. & Sofyan, H. (2020). Application of Problem Based Learning Model to Improve Problem Solving Ability of Student of XI Science Grade in Chemistry. Journal of Physics: Conference Series.Kurniawati, I.L. (2022). The Effect of Problem-Based Learning on Students' Problem-Solving and Self-Learning Abilities in Acid-Base. Jurnal Pembelajaran Kimia (J-PEK). 7(1)44-48.Kusumaningrum, L., Yamtinah, S., & Saputro, A. N.C. (2015). Pengembangan Instrumen Tes Diagnostik Kesulitan Belajar Kimia SMA Kelas XI Semester I Menggunakan Model Teslet. Jurnal Pendidikan Kimia (JPK). 4(4)36-45.Lindawati, L., Wardani, S., & Sumarti, S.S. (2019). Development of Inquiry Materials Based on Chemical Representation to Improve Students' Critical Thinking Ability. Journal of Innovative Science Education. 8(3)332-343.Melian, O.H. & Solihat, M.R. (2019). Analyzing Students' Speaking Activities in Teaching Learning Process Using STAD Method. Professional Journal of English Education (PROJECT). 2(3)257-262.Murniati, M. (2018). Application of the Problem Solving Learning Model as an Effort Improving Science Learning Achievement. Journal of Education Action Research. 2(3)249-258.Özreçberoglu, U., Çaganaga, C. K. (2018).Making It Count: Strategies for Improving Problem-Solving Skills in Mathematics for Students and Teachers' Classroom Management. Eurasia Journal of Mathematics, Science and Technology Education, 14(4):1253-1261.Pohan, A.M., Asmin., & Menanti, A. (2020). The Effect of Problem Based Learning and Learning Motivation of Mathematical Problem Solving Skills of Class 5 Students at SDN 0407 Mondang. Budapest International Research and Critics in Linguistics and Education (BirLE) Journal. 3(1) 531-539.Polya,  G.  (1971). How  To  Solve  It:  A  New  Aspect  of Mathematical   Method. USA: Princeton   University Press, Princeton, New Jersey.Purba, A., & Ramadhan, S. (2020). The Improvement of Students Mathematical Problem Solving Ability by Implementing Cooperative Learning Model in Smp Tunas Pelita Binjai. Journal of Research on Mathematics Instruction. 1(2)31-37.Rahayu, R. & Kartono. The Effect of Mathematical Disposition to Problem Solving Ability Based On IDEAL Problem Solver. International Journal of Science and Research. VOL. 3 (10)1315-1318.Rattanatumma, T. & Puncreobutr, V. (2016). Assessing the Effectiveness of STAD Model and Problem Based Learning in Mathematics Learning Achievement and Problem Solving Ability. Journal of Education and Practice. 7(12)194-199.Rohmah, A., Wardani, D.K., Noviani, L. (2018). The Use of Student Team Achievement Divisions (STAD) Cooperative Learning Models to Increase Self Efficacy and Learning Activities of Class XI Students Marketing in Retail Subjects at SMK Batik 2 Surakarta. BISE: Jurnal Bisnis dan Ekonomi.Sapuri, L., Hasratuddin, & Syahputra, E. (2017). Improving Spatial Ability and Self-Efficacy of Class VIII Students at Binjai Public Middle School 1, Langkat Regency Through STAD Type Cooperative Learning on Wingeom Assisted Geometry Material. Paradikma Journal. 10(3)1-13.Shin, M.H. (2018). Effects of Project-based Learning on Students' Motivation and Self-Efficacy. English Teaching. 73(1)95-114.Slavin, R. E. (2005). Cooperative learning: Theory, Research and Practice. London: Allymand Bacon.Tuan, H.L., Chin, & Shieh, S.H. 2005. The Development of a Questionnaire to Measure Students' Motivation Towards Science Learning. International Journal of Science Education. 27(6)639-654.Ulya, H. 2016. Profile of Highly Motivated Students' Problem Solving Ability Based on IDEAL Problem Solving. Jurnal Konseling. 2(1)90-96.Urhahne, D. (2021). Motivation to Learn and Problem Solving. Educational Psychology. 41(9)1079-1081Wehmeyer, M.L. (2007). Promoting Self-determination in Students with Developmental Disabilities. New York: The Guilford Press.Widhyastika, D. P., Sutarsyah, C., & Suparman, U. (2017). Developing Student-Team Achievement Division (STAD) Technique to Encourage Student Reading Comprehension Achievement Based on Extrovert and Introvert Personality. UNILA Journal of English Teaching. 6(2)1-11.Wu, X., Siu K.W.M., Buhring, J., & Villani, C. (2022). The Relationship between Creative Self-Efficacy, Achievement Motivation, and Job Burnout among Designers in China's e-Market. Social Sciences. 11. 509.Zubaidillah, M.H., Nuruddaoroini, M.A.S.,  & Suratno. (2022). Improving The Students' Problem-Solving Abilities Through The Development of Learning Motivation. Jurnal Ilmu Tarbiyan dan Keguruan. 25(1)149-156.